2005
DOI: 10.1093/humrep/dei011
|View full text |Cite
|
Sign up to set email alerts
|

The 2004 Italian legislation regulating assisted reproduction technology: a multicentre survey on the results of IVF cycles

Abstract: The rate of success of IVF-ICSI cycles using fresh embryos is not significantly influenced by the new legislation while the prohibition to freeze embryos seems to result in a more relevant impact.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
2
2

Year Published

2005
2005
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(40 citation statements)
references
References 16 publications
3
33
2
2
Order By: Relevance
“…However other studies showed, in contrast to ours and other authors publications, that the new legislation neither reduced success rates of assisted reproductive technologies (ART) using fresh embryos, nor increased the multiple birth rate [9,10]. Moreover La Sala et al [12].…”
Section: Incontrasting
confidence: 64%
“…However other studies showed, in contrast to ours and other authors publications, that the new legislation neither reduced success rates of assisted reproductive technologies (ART) using fresh embryos, nor increased the multiple birth rate [9,10]. Moreover La Sala et al [12].…”
Section: Incontrasting
confidence: 64%
“…Even if most Italian experts feel that the fertilization of just three oocytes could cut the success rates by about two-thirds (Turone, 2004), a recent study has shown that the efficacy of ARTs using fresh embryos is not significantly reduced (Ragni et al, 2005). Furthermore, these results were obtained in a retrospective fashion and, probably, influenced by several selection biases.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent multicentre survey (Ragni et al, 2005), the clinical impact of these limitations was evaluated, showing that the new legislation has induced only a small change in the success rate of ARTs using fresh embryos. These data are encouraging, even if altered by several biases due to the retrospective design of the study.…”
Section: Introductionmentioning
confidence: 99%
“…However, it is generally acknowledged that the reliability of current methods for predicting embryo viability requires further improvement which may arise by combining the evaluation of different parameters at successive time points. Moreover, in some countries, not all retrieved oocytes can be fertilized due to legal limitations (Ragni et al 2005). In such situations, predicting embryo quality is even more challenging because the time when the predictive evaluation can be performed is limited to the interval between oocyte retrieval and fertilization.…”
Section: Introductionmentioning
confidence: 99%